2000
DOI: 10.1074/jbc.c901035199
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Reveals Two Conformations of the 20 S Proteasome from Fission Yeast

Abstract: The proteasome is a major cytosolic proteolytic complex, indispensable in eukaryotic cells. The barrelshaped core of this enzyme, the 20 S proteasome, is built from 28 subunits forming four stacked rings. The two inner ␤-rings harbor active centers, whereas the two outer ␣-rings play a structural role. Crystal structure of the yeast 20 S particle showed that the entrance to the central channel was sealed. Because of this result, the path of substrates into the catalytic chamber has remained enigmatic. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 19 publications
7
57
0
2
Order By: Relevance
“…If these sites are located inside the particle, then the spontaneous opening of the channel (10,29) presumably enables the peptides to bind to these sites in our experiments, and thereby prevents the return of the channel to the closed conformation. The observation that potassium ions, which decrease spontaneous opening of the channel (10), delay (but do not prevent) the onset of the activation by the hydrophobic peptides (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…If these sites are located inside the particle, then the spontaneous opening of the channel (10,29) presumably enables the peptides to bind to these sites in our experiments, and thereby prevents the return of the channel to the closed conformation. The observation that potassium ions, which decrease spontaneous opening of the channel (10), delay (but do not prevent) the onset of the activation by the hydrophobic peptides (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…However, we cannot exclude the possibility that additional effects are required for maintaining the channel in the open conformation. Osmulski and Gaczynska (29) reported that blocking Suc-LLVY-amc cleavage at the chymotrypsin-like site by the inhibitor abolishes the effect of these peptides on the channel in the ␣-ring and suggested that a catalytic event is required to promote channel opening. Although the present results demonstrate that hydrophobic peptides need to bind to the non-catalytic sites to stimulate peptide hydrolysis, we cannot exclude the possibility that peptides may also have to bind to any of the catalytic sites to trigger channel opening, because in all of our experiments peptide substrates had to be present for us to assay the activities of the catalytic sites.…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of the proteasomes in the crystals did not change with time during repeated scanning. Based on AFM recordings, yeast 20 S proteasomes have been reported to switch between 2 distinct conformations (47). In contrast, the AFM images of proteasomes in two-dimensional arrays did not reveal the existence of different conformational states.…”
Section: Binding Of His-tagged Proteins To Metal-chelating Lipidmentioning
confidence: 84%
“…As outlined earlier, substrates and certain competitive inhibitors binding to orthosteric sites may double as allosteric ligands, promoting opening of the gate (99,100,103). Gate opening can be detected by AFM imaging of the 20S core and confirmed by functional studies of the latent or allosterically open core decorated with 11S activator (103).…”
Section: Allosteric Route: From the Catalytic Centers To The Grooves mentioning
confidence: 99%
“…There is one more intriguing aspect of the conformational dynamics related to effects of rapamycin. Treatment of the 20S core with the saturating concentration of a model peptide substrate induces maximum 75% of the open particles (99,100,103). A saturating concentration of rapamycin pushes the equilibrium to about 60% of the open proteasomes.…”
Section: Allosteric Route: From the Grooves On A Face To The Gatementioning
confidence: 99%